2016
DOI: 10.1186/s12864-016-3020-8
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq analysis of seasonal and individual variation in blood transcriptomes of healthy managed bottlenose dolphins

Abstract: BackgroundThe blood transcriptome can reflect both systemic exposures and pathological changes in other organs of the body because immune cells recirculate through the blood, lymphoid tissues, and affected sites. In human and veterinary medicine, blood transcriptome analysis has been used successfully to identify markers of disease or pathological conditions, but can be confounded by large seasonal changes in expression. In comparison, the use of transcriptomic based analyses in wildlife has been limited. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 42 publications
0
23
1
Order By: Relevance
“…To evaluate the performance of C3, we collected gene expression profiles from four GEO data series (GSE43013 [10], GSE74754 [11], GSE78770 [12], and GSE53393 [13]), which collectively contain data from 13 different species ( B. taurus , C. familiaris , C. porcellus , E. caballus , E. europaeus , F. catus , M. musculus , O. cuniculus , R. norvegicus , S. scrofa , D. rerio , T. truncates , and M. mulatta ) across five different tissue types (brain, kidney, liver, blood, and skeletal muscle). We tested whether C3 could correctly identify the cell type of the samples when compared against a human compendium or a mouse compendium constructed from ENCODE data [7, 8].…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the performance of C3, we collected gene expression profiles from four GEO data series (GSE43013 [10], GSE74754 [11], GSE78770 [12], and GSE53393 [13]), which collectively contain data from 13 different species ( B. taurus , C. familiaris , C. porcellus , E. caballus , E. europaeus , F. catus , M. musculus , O. cuniculus , R. norvegicus , S. scrofa , D. rerio , T. truncates , and M. mulatta ) across five different tissue types (brain, kidney, liver, blood, and skeletal muscle). We tested whether C3 could correctly identify the cell type of the samples when compared against a human compendium or a mouse compendium constructed from ENCODE data [7, 8].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to polar bear hemoglobin transcripts, the sgRNAs designed for this study will also target human hemoglobin transcripts making them useful for basic research as well as clinical applications in cancer biology and disease diagnosis ( Fig. S1) (43)(44)(45)(46). Further, the sgRNA sequences used in Long-DASH can be easily adapted to any organisms or gene.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to rhythms in hormone production, rhythmic patterns of gene expression may also underlie season and health relationships (18). Studies in humans and other animals have found seasonal patterns of gene expression in tissues such as blood (18)(19)(20) and adipose tissue (18,21), although some of these differences may also reflect seasonal changes in cell populations (22). These rhythms can vary by tissue type and share pathways with the core circadian clock system (23).…”
Section: Introductionmentioning
confidence: 99%